MAGNETIC RESONANCE IMAGING IN DIAGNOSIS AND CLASSIFICATION OF MULLERIAN DUCT ANOMALIES: CASE SERIES - BHAVYA KATARIA; SHIBANI MEHRA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Mullerian duct anomalies (MDAs) arise from the aberrant development of the uterus, cervix, and vagina, impacting the potential for successful conception and full-term pregnancy. This category encompasses a diverse range of developmental defects, leading to a spectrum of clinical presentations such as amenorrhea, infertility, recurrent miscarriages, intrauterine growth retardation, malposition of the fetus, preterm labor, and retained placenta. Case(s): In this study, we present 17 cases of MDA with a wide array of clinical manifestations. The varied symptoms included amenorrhea, infertility, repeated miscarriages, intrauterine growth retardation, malposition of the fetus, preterm labor, and retained placenta. Accurate categorization of these cases is crucial for determining the appropriate surgical intervention. While ultrasonography aids in the initial diagnosis of MDA, our focus on accurate classification necessitates the use of magnetic resonance imaging (MRI). Conclusion: Our findings underscore the significance of MRI in precisely categorizing MDA, and facilitating effective management strategies. The 17 cases presented demonstrate the diverse spectrum of MDA manifestations, emphasizing the need for tailored surgical interventions for successful conception and optimal pregnancy outcomes. The use of MRI proves instrumental in guiding clinical decisions, offering a comprehensive understanding of MDA, and informing targeted interventions to enhance reproductive success.